A Review on Ready Queue Processing Time Estimation Problem and Methodologies used in Multiprocessor Environment - More, Sarla; Shukla, Diwakar (International Journal of Computer Sciences and Engineering, 2025)
CPU scheduling is a technique by which the processes in the system are able to be allocated the processor and by execution they perform their intended task. In order to this various scheduling schemes are available with their own merits and demerits. Lottery scheduling is one of the best algorithms to schedule the processes for the processor so that all processes get executed with the ease of convenience with better efficiency. Lottery scheduling solves many problems of previous scheduling schemes, starvation is one of them, flexible and fair share of resources to each and every process is possible with this scheme. This paper illustrates the various methods provided in the field of CPU scheduling and in the basic function of operating system that is process management to calculate the ready queue estimation time. Ready queue is responsible for holding the processes which needs to be allocated to the CPU for execution. It contains heterogeneous type of processes from the multiprocessor environment. The lottery scheduling scheme allows each process with its specific characteristics to share the resources and execute accordingly. Processes have the dynamic characteristics of creation, activation, waiting, execution, sharing, pre-emption, interruption and termination. The time spent by the processes in the ready queue waiting for CPU is a crucial time because it predicts the performance efficiency of the CPU. The problem of time estimation of ready queue processing is represented in this paper with various associated constraints to better evaluate the results. The working of lottery scheduling scheme and various algorithms which are derived from it are represented here. The summarized version of the existing work represented here to better understand the problem and predict the new possibilities in this area.